"It's how you live"- understanding culturally embedded entrepreneurship: an example from Solomon Islands. Issue 6 (18th August 2022) - Spann, Michael
ABSTRACT: This article adds to critical discussions around entrepreneurship in the Pacific. By drawing on an example of an entrepreneur from rural Solomon Islands, it illustrates how complex negotiations between cultural and commercial imperatives affect and influence cultural and economic decision making. The objective of this article is to argue for a more inclusive conception of entrepreneurship in development strategies; one that shifts from a narrow economic focus to consider entrepreneurship as a relational practice across possessive and distributive economic agencies to better understand the social, cultural, and economic goals that motivate and influence indigenous entrepreneurs.